Reducing the climate impact of a building in the design phase -Identifying focus areas in the design phase - Boberg, John; Håkansson, Per (My University, 2020)
Some of the largest actors within the building sector have recently introduced road maps and goals to make the industry more sustainable. In order to establish a focus area for sustainable building development, this study looks to determine what elements and sections of a building contributes to the largest amount of greenhouse gas emissions. Additionally, the reader gets to follow an investigation into what possible measures and changes a structural engineer can make to reduce and improve the climate impact of the design of a building as well as what obstacles hinders the progress. The study has been made in collaboration with the building structures department at WSP Sweden in Gothenburg. To sufficiently cover such a broad subject area, the study was carried out in three different sections. Firstly, a literature study was conducted on relevant papers, literature and industry standards. Additionally, research was also made into what sustainability goals have been set within the building industry. Secondly, an interview study was conducted with stakeholders at the building structures department at WSP. The group of interviewees were chosen to be of differing positions, experience and insight into sustainable building technology to garner several perspectives and arguments. Additionally, a survey was sent out to the building structures department to accumulate a more quantitative result for certain matters. The third and final section was a case study that was built upon the results of the interviews. The purpose of it was to visualise the amount of greenhouse gases that originate from the concrete in two separate hospital buildings, as well as the impact of the measures proposed in the interviews. The measures investigated were a reduction of concrete volume by reducing the thickness of all walls and slabs, lowering the concrete class of all concrete in the building and the impact of various amounts of steel reinforcement in the floor slabs. The primary conclusion that can be drawn from this study is that there are large possibilities to reduce the greenhouse gas emissions of the building process, but the implementation is complex in the current industry climate. The case study demonstrates that the reduction of wall and slab thickness, as well as the lowering of concrete classes had a substantial impact on the buildings total greenhouse gas emissions. The majority of measures lifted in the interview study may also have a significant impact from a sustainable perspective, but often come with costs or risks in different aspects. Due to this, it is important to find optimum balance between different aspects, which is time-consuming. This has resulted in a great push for a more streamlined, user-friendly and restructured design process as it would help the industry to focus more on optimization. There is a strong consensus that this can change with further knowledge and experience of sustainable building technology.
Keywords: sustainable building, greenhouse gas, emissions, structural engineer, climate impact, building industry, concrete, steel reinforcement, design process, optimization v